Multicentric Castleman's Disease in a Child Revealed by Chronic Diarrhea. (9th February 2015) - Benmiloud, Sarra; Chaouki, Sana; Atmani, Samir; Hida, Moustapha
Abstract : Multicentric Castleman's disease is a rare benign and unexplained lymphoproliferative disorder that is extremely uncommon in children. It presents with fever, systemic symptoms, generalized lymphadenopathy, and laboratory markers of inflammation. Its treatment is not standardized and its prognosis is poor. We report a novel case of multicentric Castleman's disease in a 13-year-old girl who had presented with chronic diarrhea as the only initial presenting symptom. The diagnosis of celiac or inflammatory bowel diseases was suspected, but two and a half years later, the diagnosis of multicentric Castleman's disease was brought following the appearance of abdominal mass whose biopsy revealed Castleman's disease in the plasma cell form. The outcome was favorable after treatment by corticosteroid, chemotherapy, and surgery. The occurrence of diarrhea as the initial symptom of multicentric Castleman's disease without lymph node involvement is very rare. This case report underlines the diagnostic difficulties and the long interval between onset and diagnosis when diarrhea occurs first.